Complementary epitopes and favorable developability of monoclonal anti-LAMP1 antibodies generated using two transgenic animal platforms. - Beatrice Cameron; Tarik Dabdoubi; Laurence Berthou-Soulié; Marie Gagnaire; Isabelle Arnould; Anne Severac; Fabienne Soubrier; Jacqueline Morales; Philip A Leighton; William Harriman; Kathryn Ching; Yasmina Abdiche; et al. (PLoS ONE)
Monoclonal antibodies (mAbs) for therapeutic applications should be as similar to native human antibodies as possible to minimize their immunogenicity in patients. Several transgenic animal platforms are available for the generation of fully human mAbs. Attributes such as specificity, efficacy and Chemistry, Manufacturing and Controls (CMC) developability of antibodies against a specific target are typically established for antibodies obtained from one platform only. In this study, monoclonal antibodies (mAbs) cross-reactive against human and cynomolgus LAMP1 were derived from the human immunoglobulin transgenic TRIANNI mouse and OmniChicken® platforms and assessed for their specificity, sequence diversity, ability to bind to and internalize into tumor cells, expected immunogenicity and CMC developability. Our results show that the two platforms were complementary at providing a large diversity of mAbs with respect to epitope coverage and antibody sequence diversity. Furthermore, most antibodies originating from either platform exhibited good manufacturability characteristics.